The Historical Account in the Myth: Enrique Líster and the Battle of Words - Galán Ortega, José (Madrygal. Revista de Estudios Gallegos, 2020)
This article intends to explore the existing conections among the accounts of war experience, the memory of the protagonist of the narrated war events and the cultural dimension of the emotions projected in the texts and other autobiographical documents (fear, compasión, pride...) created by Enrique Líster Forján, the Galician military and communist leader. The methodology chosen for this work applies an approach from cultural history to the different contexts of writing and the most important elements of the interpretation focused on concepts such as comradeship and masculinity by a comunist militant committed to the construction of a new world, to stop the fascist advance on Spain and Europe and, later on, in the overthrowal of the francoist dictatorship. A continuous fight carried out until the end by discursive means, and the transformation of the defeat suffered against Franco and his nazi-fascist allies into a mobilizing story that handles the epic in a selective way and as a strategy to grant the people a privileged role in the regeneration of their historical destiny.